2012
DOI: 10.1007/s10750-011-0916-9
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal concentrations in the tropical sponge Spheciospongia vagabunda at a sewage outfall: synchrotron X-ray imaging reveals the micron-scale distribution of accumulated metals

Abstract: Major and trace elements were measured in sponges, seawater and sediment in Darwin Harbour (Australia) to test the hypothesis that metals are elevated in sponges closer to a sewage outfall compared with unimpacted sites. Seawater and sediment at the sewage discharge site contained high, but localised, concentrations of phosphorus (P), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), arsenic (As) and lead (Pb) compared with background sites. Metal concentrations in the sponge Sphecio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 37 publications
(46 reference statements)
2
9
1
Order By: Relevance
“…Value of 1 was set as threshold for all analytes, with results equal or above 1 being considered indicative of bioconcentration. When TE concentration in seawater is included in the study, the BAF are also calculated by dividing the TE sponge's content by the one found in seawater (Padovan et al, 2012;Venkateswara Rao et al, 2009;Batista et al, 2014).…”
Section: Te Bioaccumulation In Spongesmentioning
confidence: 99%
See 1 more Smart Citation
“…Value of 1 was set as threshold for all analytes, with results equal or above 1 being considered indicative of bioconcentration. When TE concentration in seawater is included in the study, the BAF are also calculated by dividing the TE sponge's content by the one found in seawater (Padovan et al, 2012;Venkateswara Rao et al, 2009;Batista et al, 2014).…”
Section: Te Bioaccumulation In Spongesmentioning
confidence: 99%
“…Sponges pump large quantities of seawater (100-1200 mL h −1 g −1 ), more than any other marine invertebrates (Olesen and Weeks, 1994). These organisms have a high capacity for TEs accumulation (Patel et al, 1985;Padovan et al, 2012), exhibiting higher filtering capacity than bivalves (Negri et al, 2006;Gentric et al, 2016). They are considered as "biological particle traps" due to their ability to concentrate a wide range of chemicals from both the suspended and dissolved phases of the water, with usually high bioconcentration factors (BCF) (Perez et al, 2005;Cebrian et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Using a collimated beam, larger objects, such as works of art, have been imaged at 50-100 µm resolution [18] over areas up to 600 × 300 mm 2 . This method has been applied to studies in the earth [23][24][25][26][27][28][29][30], planetary [31], environmental [32,33], medical [19,34], biological [20][21][22][35][36][37][38][39][40][41] and material [42] sciences as well as cultural heritage [18,43]. A similar capability has been established on the P06 beamline (e.g.…”
Section: Large Area Mappingmentioning
confidence: 99%
“…As a matter of fact, marine sponges have been studied more comprehensively than those from the Baikal Lake. The structure of sponge spicules, the water content in sponges, density, and biochemical and element composition have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The average chemical composition of their spicules was 85.2% SiO 2 , 12.3% water, and 2.5% of some other elements such as S, Al, K, Ca, and Na. References refer to marine sponges as biomonitors of environment, for they are known to have a strong ability to concentrate metals in their tissues . The metal concentrations were measured by ICP‐MS, AAS, X‐ray fluorescence microprobe analysis, and energy‐dispersive X‐ray fluorescence spectrometry (EDXRF).…”
Section: Introductionmentioning
confidence: 99%